The effect of surface roughness on oblique bicycle helmet impact tests - Petersen, P. G.; Smith, L. V.; Nevins, D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
The friction between a helmet and impact surface affects the accelerations imparted to the head. The roughness of the impact surface is, therefore, a consideration when developing oblique impact standards. An 80-grit abrasive paper is commonly used in oblique impact tests to simulate a road surface, but has not been validated for bicycle impacts and may not accurately represent real road surfaces. In the following study, a helmeted NOCSAE headform with a Hybrid III neck was dropped onto a 45° anvil at 6.5 m/s using a twin wire guided drop tower. Helmeted drops were performed in two orientations (frontal and side) on road surfaces, roughened steel surfaces, 80-grit abrasive paper and a low friction surface. For each impact, measures of linear and rotational acceleration were obtained. These metrics were compared across impact orientations and surfaces to assess the influence of surface roughness on headform impact response. Frontal impacts were less sensitive to the impact surface roughness than side impacts across metrics. Among metrics, rotational acceleration showed the largest effect due to surface roughness. Compared to the road surface, peak rotational acceleration from impacts on the 80-grit surface were 6.5% less and 48% greater for frontal and side impacts, respectively. Based on consideration of the peak and cumulative impact measures, steel impact surfaces appear to better simulate road impact than the commonly used 80-grit abrasive paper.